The mobile film van as a communications medium in environmental education - T Monchusi; P Hancock (Environmental Association of Southern Africa, 1986)
This paper describes an elementary evaluation of a mobile film van as a comnunications medium in the environmental education progranme of the National Parks Board of Bophuthatswana.